IMPLEMENTASI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN PEMBELAJARAN EFEKTIF BAGI GURU DI SMKS BUDI UTOMO BINJAI - Alfredo Ginting, Jerry Evan; Maulana Akbar Sanjani; Lendra Faqrurrowzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of principal supervision in improving effective learning among teachers at SMKS Budi Utomo Binjai. The problem addressed in this research is the suboptimal effectiveness of classroom learning, which is indicated by limitations in instructional organization, communication, classroom management, and the use of varied learning methods. The purpose of this study is to analyze how principal supervision is planned, implemented, evaluated, and adapted to teachers with different professional backgrounds in order to enhance effective learning. This research employed a descriptive qualitative approach. Data were collected through observations, in-depth interviews with the principal and teachers, and documentation related to supervision activities. The data were analyzed using qualitative descriptive techniques involving data reduction, data display, and conclusion drawing, with data validity ensured through source triangulation. The findings indicate that effective supervision is achieved through structured planning, direct classroom observation, collaborative and humanistic approaches, and continuous follow-up in the form of coaching and training. In addition, adaptive supervision strategies tailored to teachers’ varying competencies contribute to improved teaching practices, increased student engagement, and the emergence of instructional innovations. Overall, principal supervision plays a strategic role in improving the quality and effectiveness of learning at the school.